Socio-family context that favors emotional intelligence in adolescents: a review - Iñipe Cachay, Milagros (2023)
The socio-familiar context has been blamed for multiple events, both favorable and unfavorable, even more so in the development of children and adolescents; In accordance with this reality, the objective of this review article is to analyze the scientific literature that reveals the way in which the socio-family context favors emotional intelligence in adolescents. We worked under the guidelines of the PRISMA systematization matrix, where the databases analyzed were SCOPUS, PUBMED, SCIELO, REDALYC, with 3444 articles found between 2018 and 2022 respectively, after the selection process, 14 articles that met the criteria were analyzed. the criteria established by the investigator. The main findings are about adolescents who live and interact within an appropriate socio-family context, characterized by continuous and timely attention from parents, assertive dialogue, affective climate, practice of positive values, good family customs, among others. They present a greater development of their capacities to identify and respect their own emotions and those of others, which leads adolescents to be more proactive and show a positive attitude towards the various circumstances they face. Thus, it was concluded that the socio-family context favors the development of emotional intelligence in adolescents.